2014
DOI: 10.1136/emermed-2014-203871
|View full text |Cite
|
Sign up to set email alerts
|

When should we use diagnostic imaging to investigate for pulmonary embolism in pregnant and postpartum women?

Abstract: Pulmonary embolism (PE) is a leading cause of death in pregnancy and postpartum. Clinicians face a difficult choice when deciding whether to use diagnostic imaging to investigate for suspected PE in these patients, between risking potentially catastrophic consequences of missed diagnosis if imaging is withheld and risking unnecessary iatrogenic harm to both mother and fetus if imaging is overused. This paper explores the options for imaging and evidence for the use of clinical features, clinical predictions sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…7 Participants were asked to rate the predictive value of each variable on a 1 (not predictive) to 5 (very strongly predictive) Likert scale and to justify their opinion in free text. A mixed-methods approach was taken to summarise each round's findings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Participants were asked to rate the predictive value of each variable on a 1 (not predictive) to 5 (very strongly predictive) Likert scale and to justify their opinion in free text. A mixed-methods approach was taken to summarise each round's findings.…”
Section: Methodsmentioning
confidence: 99%
“…In January 2014, we systematically searched electronic databases for diagnostic studies of pregnant or postpartum women undergoing imaging for a suspected PE 7 and identified 11 relevant articles, along with a conference abstract and a paper in press. We have since updated the literature searches and have identified an additional four papers, along with the published version of the paper in press.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[1] Existing clinical decision rules (CDRs) to guide imaging decisions in PE include d-dimer testing, which has been shown to be unreliable in pregnancy. [2] Current guidelines consequently recommend that all pregnant or postpartum women with suspected PE should receive advanced diagnostic imaging. [3] However this non-selective approach results in very low rates of detected PE, risks radiation exposure and reaction to contrast media, is inconvenient for patients, and incurs costs for the health services.…”
mentioning
confidence: 99%
“…The open first round of the classical Delphi approach was replaced with a systematic literature review to identify possible PE predictors. [2] Participants were then asked to rate the predictive value of each variable on a 1 to 5 Likert scale and justify their opinion. In subsequent Delphi iterations, participants were provided with quantitative and qualitative results of the previous round, and a summary of their previous opinions.…”
mentioning
confidence: 99%
See 1 more Smart Citation